2010
DOI: 10.1007/s00442-010-1644-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal patterns in shorebird nest survival are related to nest age and defence behaviour

Abstract: Nest survival may vary throughout the breeding season for many bird species, and the nature of this temporal variation can reveal the links between birds, their predators, and other components of the ecosystem. We used program Mark to model patterns in nest survival within the breeding season for shorebirds nesting on arctic tundra. From 2000 to 2007, we monitored 521 nests of five shorebird species and found strong evidence for variation in nest survival within a nesting season. Daily nest survival was lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 59 publications
10
76
2
Order By: Relevance
“…Dinsmore et al (2002) also found that Mountain Plover (Charadrius montanus) nest survival increased with nest age. As nest age increases, adults have invested more in the nest and typically increase defensive behavior as a result (Smith and Wilson 2010). Similar to our findings, Johnson and Walters (2008) found a negative relationship between nest survival and nest age in Western Sandpipers (Calidris mauri) and suggested that this effect was more important for pairs nesting in the area for the first time.…”
Section: Discussionsupporting
confidence: 87%
“…Dinsmore et al (2002) also found that Mountain Plover (Charadrius montanus) nest survival increased with nest age. As nest age increases, adults have invested more in the nest and typically increase defensive behavior as a result (Smith and Wilson 2010). Similar to our findings, Johnson and Walters (2008) found a negative relationship between nest survival and nest age in Western Sandpipers (Calidris mauri) and suggested that this effect was more important for pairs nesting in the area for the first time.…”
Section: Discussionsupporting
confidence: 87%
“…Initiating breeding early in the season maximizes the time available for fledgling development as well as for second or replacement clutches. However, nesting earlier may involve increased nest failure, resulting from more inclement weather or from higher predation risk due to easier detection by, or greater energetic needs of, predators (Byrkjedal 1980, Martin and Wiebe 2004, Smith and Wilson 2010. Breeding later in the season may incur lower risks related to inclement weather, but then the time to produce a second brood or a replacement clutch is restricted (Barba et al 1995, Wilson and Martin 2008, Martin 2014.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown experimentally that passerines can adjust their incubation behavior in response to the presence or absence of predators (Fontaine and Martin 2006). Variation in clutch survival among Arctic shorebird species has been related to whether species show uniparental or biparental incubation (Smith and Wilson 2010) and is correlated with the total time spent off the nest .…”
Section: Discussionmentioning
confidence: 99%